2020
DOI: 10.1111/and.13504
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating impact of hydroethanolicMurraya koenigiileaves extract on bisphenol A instigated testicular lethality and apoptosis in mice

Abstract: Bisphenol A (BPA) is a well‐known endocrine disruptor that imposees adverse effects on male fertility via interacting with germ cells of testis. Objectives of present study were to investigate the possible protective effects of hydroethanolic Murraya koenigii leaves extract (HEMKLE) against BPA‐induced testicular damage and apoptosis in mice. Male Balb/c mice were divided into four different groups: Group I (control), Group II (HEMKLE), Group III (BPA) and Group IV (HEMKLE + BPA). Group III (BPA) showed signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 76 publications
2
11
0
Order By: Relevance
“…Likewise, in present study, mRNA and protein expression analysis revealed a marked reduction in the expression of Bcl‐2 and an upregulation in the caspase‐9, caspase‐8 and caspase‐3 in BPA‐treated group, which demonstrate apoptosis. Previous studies also confirmed a similar trend of an increased expression of caspase‐9 and caspase‐3 upon BPA exposure (Kaur et al., 2020; Li et al., 2009; Xia et al., 2014). A study by Qian et al.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Likewise, in present study, mRNA and protein expression analysis revealed a marked reduction in the expression of Bcl‐2 and an upregulation in the caspase‐9, caspase‐8 and caspase‐3 in BPA‐treated group, which demonstrate apoptosis. Previous studies also confirmed a similar trend of an increased expression of caspase‐9 and caspase‐3 upon BPA exposure (Kaur et al., 2020; Li et al., 2009; Xia et al., 2014). A study by Qian et al.…”
Section: Discussionsupporting
confidence: 75%
“…A significant decline in the activities of SOD, CAT and GSH/GSSG ratio, whereas a noticeable increase in the GST activity was observed in the BPA‐induced mice when compared to control mice, which showed toxic effects (increasing the OS) of BPA on the mice testis . Previously published reports also evidenced the BPA‐incited toxicity via disrupting the antioxidant defence system and excess ROS generation (Kaur & Sadwal, 2020; Kaur et al., 2018, 2020). However, Se supplementation restored the activities of all these in Se co‐treated group, presenting its role in eliminating free radicals, and this might be the fundamental compensatory mechanism to avoid the development of the OS.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…1 One of the known reason of BPA toxicity is the induction of oxidative stress, 3 which disrupts the male and female reproductive systems. 6 Many studies have shown that BPA can decreases the levels of antioxidant enzymes 7,8 although, can increases malondialdehyde (MDA) levels 7,8 and other oxidative stress factors, 9,10 In following that, it can degenerate germinal epithelium, 11,12 besides, it causes degradation in the sperm quality and quantity, 11,12 testosterone levels, as well as, spermatogenesis. 13 It is undeniable that the oxidative stress property of BPA is one of the most important reasons for its toxicity, therefore, in this study, Vitamin E (VE) was used as a potent antioxidant to neutralize the free radicals created by BPA.…”
Section: Introductionmentioning
confidence: 99%
“…As another example, Murraya koenigii leaf extract exerts a protective effect in mouse orally administered BPA. M. koenigii exerts protective effects against BPA by improving sperm parameters, and decreasing lipid peroxidation and ROS levels in mouse testis [68]. Gallic acid, another natural antioxidant, is commonly found in fruits and vegetables.…”
Section: Other Natural Antioxidantsmentioning
confidence: 99%